PENGARUH DIFERENSIASI PRODUK DAN BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN GOODTEA DI GAJAH MADA PLAZA - Agus, Tri; Wiwaha, Arjuna (L2Dikti Wilayah III, 2020)
Goodtea is a trademark of a system of ready-to-drink tea beverage business opportunities that offers a choice of diverse and quality flavors. Where consumers can enjoy tea drinks that are beneficial to health, delicious and varied flavors. This study discusses the problem of the influence of product differentiation and promotional mix on purchasing decisions. The purpose of this study was to determine the magnitude of the effect of product differentiation and promotion mix simultaneously on purchasing decisions. The research method used is library research and field research. Data collection techniques using questionnaires, interviews and observations. The population in this study is GOODTEA consumers in Gajah Mada Plaza estimated as many as 2400 customers each month. This study used 240 samples. This study uses SPSS V.23 to calculate, process and analyze research data. The results of the study show that there is a strong and significant influence between product differentiation and promotion mix simultaneously on purchasing decisions of 41,4%